Resveratrol elongates the lifespan and improves antioxidant activity in the silkworm Bombyx mori - Jiangbo Song; Lian Liu; Kaige Hao; Shuang Mao; Yongxi Tang; Xiaoling Tong; Fangyin Dai (Elsevier, 2021)
A number of research has shown that the plant polyphenol resveratrol, one of the most prominent small molecules, has beneficial protective effects in multiple organisms, including worms, flies, and killifish. To understand the effects of resveratrol on lifespan, we evaluated its effects in the silkworm Bombyx mori. In this study, we found that lifespan was significantly prolonged in both female and male silkworms treated with resveratrol. Silkworm larval weight was significantly increased from day 3 of the 5th larval instar (L5D3) to day 7 of the 5th larval instar (L5D7). However, the weight of the pupa, cocoon, and total cocoon was not significantly different in female silkworms with resveratrol treatment than that in controls. Meanwhile, resveratrol significantly improved the thermotolerance of the silkworms, which enhanced their survival rate. Moreover, antioxidant activity was increased by resveratrol in both female and male silkworms. Furthermore, an antioxidant-related signalling pathway, SIRT7-FoxO-GST, was activated in silkworms with resveratrol treatment. Collectively, these results help us to understand the molecular pathways underlying resveratrol induced pro-longevity effects and indicate that silkworm is a promising animal model for evaluating the effects of lifespan-extending drugs.